AN OVERVIEW OF ROMANIAN RURAL DEVELOPMENT PROGRAMME 2014-2020 IMPLEMENTATION - LAURA CIOBANU (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2021)
Romania had to spend in 2014-2020 for rural development € 9.5 billion of which € 8.1 billion from the European Fund for Rural Development (EAFRD) budget and € 1.4 billion national co-financing. Although the total budget and its distribution by year remained unchanged during the programming period, the allocation of funds by priorities and measures underwent several changes, mainly due to the intermediate results of implementation. This paper aims to identify the extent to which Romania has accessed European funds for rural development in the 2014- 2020 period and to offer an overview of Rural Development Programme (RDP) 2014-2020 implementation. It will emphasise which measures were least accessed and how the current situation of the results shows compared to the initial targets. The data were mainly taken from the official website of the National RDP 2014 - 2020. The analysis of the degree milestones achievement shows that the minimum threshold of 85% has been reached for all program priorities so far. All the alternative indicators established by the program and 5 of the 7 main indicators established at the level of all priorities have reached their milestone (stage objective?) in proportion of 100%. Currently, priorities 2, 4 and 6 have the highest chances of recording maximum values of the result indicators at the end of the period, as they have exceeded the 85% threshold within the milestones Although there was no perfect match between the programmed financial support and the Romanian rural reality, RDP 2014-2020 managed to respond largely to the needs of agriculture and rural space as a whole. The progress that Romania has made in terms of rural development is largely due to the measures implemented by the RDP during the last programming period. The results show that although there was no perfect match between the programmed financial support and the Romanian rural reality, RDP 2014- 2020 managed to respond largely to the needs of agriculture and rural space as a whole.